2018
DOI: 10.1159/000494822
|View full text |Cite
|
Sign up to set email alerts
|

A Familial Small Supernumerary Marker Chromosome 15 Associated with Cryptic Mosaicism with Two Different Additional Marker Chromosomes Derived de novo from Chromosome 9: Detailed Case Study and Implications for Recurrent Pregnancy Loss

Abstract: We report a case of familial small supernumerary marker chromosome 15 in a phenotypically normal female with 4 recurrent spontaneous abortions and a healthy child. The initial karyotype showed a small, bisatellited, apparently metacentric marker chromosome, 47,XX,+idic(15)(q11.1), maternally inherited. The proband's mother was mosaic for the idic(15)(q11.1) without pregnancy loss. Reexamination of the proband's karyotype revealed cryptic mosaicism for 1 ring and 1 minute chromosome derived de novo from chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…An increased rate of recurrent abortions in sSMC carriers has been seen in 26-37% of the cases (20). This cannot precisely define the potential risk of spontaneous abortions caused by sSMCs (21). Infertile patients have a higher frequency of sSMCs than the general population (0.125% vs. 0.044%); it is also higher in infertile males (0.165%) than the females (0.022%) (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased rate of recurrent abortions in sSMC carriers has been seen in 26-37% of the cases (20). This cannot precisely define the potential risk of spontaneous abortions caused by sSMCs (21). Infertile patients have a higher frequency of sSMCs than the general population (0.125% vs. 0.044%); it is also higher in infertile males (0.165%) than the females (0.022%) (18).…”
Section: Discussionmentioning
confidence: 99%
“…sSMC (small supernumerary marker chromosome) is an extra chromosome. sSMC can originate from any of the 24 different human chromosomes and its origin cannot be identified using conventional-banding cytogenetic techniques (19). An increased rate of recurrent abortions in sSMC carriers has been seen in 26-37% of the cases (20).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many groups have reported that chromosomal aneuploidies were detected in the POCs in several cases with a history of RPL and normal karyotype of fibroblasts or lymphocyte genome. Their results revealed that maternal mosaicism most probably gives rise to embryonic chromosome aneuploidies [ 68 ], [ 69 ], [ 70 ], [ 71 ]. Recently, Ghevaria et al.…”
Section: Maternal and Paternal Genetic Factors Account For Rplmentioning
confidence: 99%
“…Cryptic mosaicism in the germ layer of the gonad has been proposed as one of the possible causes of unexplained chromosomal abnormalities in the fetus. Nevertheless, parental gonadal mosaicism should be considered when the karyotype is normal and a specific abnormality is recurrently observed[91][92][93]. It has been suggested that the genomic instability found in POC samples obtained from RPL families may be caused by genetic disorders that occur either during parental or at the postzygotic stage due to the function of the embryonic genome.…”
mentioning
confidence: 99%